The importance of addressing multiple risk markers in type 2 diabetes: Results from the LEADER and SUSTAIN 6 trials. Issue 2 (5th November 2021) - Zobel, Emilie H.; von Scholten, Bernt Johan; Hansen, Tine W.; Persson, Frederik; Rasmussen, Søren; Wolthers, Benjamin; Rossing, Peter
Abstract: Aims: To investigate to what extent multiple risk marker improvements confer lower risk of cardiovascular and kidney complications in a contemporary type 2 diabetes population. Materials and methods: Post‐hoc analysis of the LEADER (n = 8638; median follow‐up 3.8 years) and SUSTAIN 6 (n = 3040; median follow‐up 2.1 years) cardiovascular outcome trials. Participants were those with baseline and year‐1 assessment of at least one of the parameters of interest; we pooled the liraglutide‐/semaglutide‐ and placebo‐treated groups and categorized them by number of risk markers with clinically relevant improvements after 1 year of study participation. We investigated risk of major adverse cardiovascular events (MACE), expanded MACE, cardiovascular death and nephropathy. Predefined clinically relevant changes: body weight loss ≥5%; reductions in: glycated haemoglobin ≥1%, systolic blood pressure ≥5 mmHg and low‐density lipoprotein cholesterol ≥0.5 mmol/L; estimated glomerular filtration rate change ≥0 ml/min/1.73 m 2 and urinary albumin‐to‐creatinine ratio change ≥30% of baseline value. Cox regression analysed risk of outcomes adjusted for baseline risk marker levels and treatment group and stratified by trial. Results: Participants with two, three, or four or more improved risk markers versus participants with no risk marker improvement had reduced risk of expanded MACE [hazard ratio (95% confidence interval) 0.80 (0.67‐0.96); 0.80 (0.66‐0.97); 0.82 (0.66‐1.02)], cardiovascular death [0.66 (0.45‐0.96), 0.67 (0.45‐0.99), 0.60 (0.38‐0.94)] and nephropathy [0.71 (0.52‐0.97), 0.48 (0.34‐0.68), 0.43 (0.29‐0.65)]. Conclusions: In persons with type 2 diabetes, improvements in ≥2 risk markers conferred cardiovascular risk reduction versus none or one improved risk marker. The nephropathy risk decreased with improvement in more risk markers. These findings stress the importance of multifactorial interventions targeting all risk markers.